Linear IgA bullous dermatosis and elevated bullous interleukin‐6 levels: Responsive to treatment with Anti‐IL‐6 receptor monoclonals. Issue 2 (27th February 2023) - Jordan, Stanley C.; Balzer, Bonnie; Nast, Cynthia; Atienza, Janet; Lim, Katherine; Kumar, Sanjeev; Nissen, Nicholas; Shin, Bongha
Abstract: Linear IgA bullous dermatosis (LABD) is  a rare autoimmune/inflammatory skin condition. Here, we report on a patient who developed treatment resistant LABD. At diagnosis, elevations of IL‐6 and C‐reactive protein in the blood and extreme elevations of IL‐6 in LABD bullous fluid were seen. The patient responded well to tocilizumab (anti‐IL‐6 receptor) treatment.